Analisis eksergi pengering tipe bak untuk pengeringan simplisia herbal - Hendri Syah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The drying of herb in packed bed is a complex process that involves the simultaneous heat and mass transfer between the air and product. Thermodynamic analysis particularly exergy analysis to be an essential tool for evaluates the avaiable energy at different point in a drying system and provides the useful information for redisign.The objective of this study are determined destruction exergy and eficiency exergy of packed bed dryer for herb drying. A packed bed dryer used for drying experiments. This apparatus that has been prepared with the PID temperature control system. The drying experiments were conducted at different three sample height in bed of 10 cm,20 cm, and 30 cm. Air velocity that is used varied 0.4 m/s and 0.6 m/s. The result showed air temperature in bed decreases with distence because more heat is being transfered to the herb by increasing the distance from inlet of the bed. The highest average destruction exergy was15,015 kJ/s at air velocity 0,6 m/s and sample height 30 cm. The lowest value of average exergy eficiency was 23,59% ..at air velocity 0,6 m/s and sample height 10 cm. It was concluded that exergy eficiency decreased with increasing air velocity